The Mediating Role of OCB On Employee Performance: The Effect of Discipline and Work Motivation: Study at One Government Agency in Malang - Aan Aiditiar; Ilfi Nur Diana (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Employee performance is a critical factor that organizations and companies must maintain and enhance, as it directly influences their effectiveness and success. This study aims to investigate the impact of work discipline and work motivation on employee performance, with Organizational Citizenship Behavior (OCB) serving as a mediating variable in a government agency in Malang City. Employing a quantitative method through explanatory research, the analysis utilized Smart PLS 4.0 with a sample of 46 respondents. The findings indicate that work discipline does not significantly affect employee performance, paralleling the results for work motivation, which also shows no significant impact on performance. However, OCB effectively mediates the relationship between work discipline and employee performance, suggesting that employees’ voluntary behaviors play a crucial role. Conversely, OCB does not serve as a mediator between work motivation and employee performance. The implications of this research highlight the need for organizations to focus on cultivating OCB to enhance the effectiveness of work discipline on performance outcomes. Ultimately, fostering a supportive environment that encourages voluntary contributions may be more beneficial than solely emphasizing motivational factors, which may not have the anticipated direct impact on performance. Thus, organizational leaders are encouraged to implement strategies that promote a culture of OCB, contributing to overall employee engagement and organizational success.